Penyuluhan Hukum Mengenai Hukum Perkawinan di Desa Waworaha Kecamatan Soropia Kabupaten Konawe - Hasima, Rahman; Sirjon, Lade; Nazar, Muh. (Fakultas Hukum Universitas Semarang, 2024)
The birth of Law Number 1 of 1974 concerning Marriage as a legal basis in the implementation of marriage but there are still many problems that occur such as lack of public understanding of the age limit for marriage and marriage registration, economic problems causing child marriage and do not have costs for the administration of marriage registration, and most people think that marriage under religious law alone is sufficient in legalizing the relationship between the two The couple does not need to be recorded in the marriage book. The method of implementing community service activities is in the form of legal counseling on marriage law in Waworaha Village, Soropia District, Konawe Regency. Legal counseling is carried out by conveying directly to the public regarding the norms in the Marriage Law, especially related to the age limit for marriage and marriage registration. The methods used during the process of community service activities include lecture and question and answer methods to explore public knowledge of the material provided. The results of the activity showed that legal counseling can increase the understanding and knowledge of the people of Waworaha Village related to the regulations in Law Number 1 of 1974 concerning Marriage, especially the provisions for the age limit for marriage and marriage registration aimed at increasing public understanding and knowledge related to the provisions of the age limit for marriage before legal counseling activities are carried out by 50% and after counseling activities are carried out An increase to 90% and an increase in public understanding regarding marriage registration before legal counseling activities were carried out by 50% and after legal counseling activities were carried out also increased by 85% which can be shown by participants' participation in participating in legal counseling activities from the beginning to the end of the activity with questions asked by participants in the question and answer session.